Dissection of Root Transcriptional Responses to Low pH, Aluminum Toxicity and Iron Excess Under Pi-Limiting Conditions in Arabidopsis Wild-Type and stop1 Seedlings - Ojeda-Rivera, Jonathan Odilón; Oropeza-Aburto, Araceli; Herrera-Estrella, Luis (Frontiers in Plant Science, 2020)
Acidic soils constrain plant growth and development in natural and agricultural ecosystems because of the combination of multiple stress factors including high levels of Fe3+, toxic levels of Al3+, low phosphate (Pi) availability and proton rhizotoxicity. The transcription factor SENSITIVE TO PROTON RHIZOTOXICITY (STOP1) has been reported to underlie root adaptation to low pH, Al3+ toxicity and low Pi availability by activating the expression of genes involved in organic acid exudation, regulation of pH homeostasis, Al3+ detoxification and root architecture remodeling in Arabidopsis thaliana. However, the mechanisms by which STOP1 integrates these environmental signals to trigger adaptive responses to variable conditions in acidic soils remain to be unraveled. It is unknown whether STOP1 activates the expression of a single set of genes that enables root adaptation to acidic soils or multiple gene sets depending on the combination of different types of stress present in acidic soils. Previous transcriptomic studies of stop1 mutants and wild-type plants analyzed the effect of individual types of stress prevalent in acidic soils. An integrative study of the transcriptional regulation pathways that are activated by STOP1 under the combination of major stresses common in acidic soils is lacking. Using RNA-seq, we performed a transcriptional dissection of wild-type and stop1 root responses, individually or in combination, to toxic levels of Al3+, low Pi availability, low pH and Fe excess. We show that the level of STOP1 is post-transcriptionally and coordinately upregulated in the roots of seedlings exposed to single or combined stress factors. The accumulation of STOP1 correlates with the transcriptional activation of stress-specific and common gene sets that are activated in the roots of wild-type seedlings but not in stop1. Our data indicate that perception of low Pi availability, low pH, Fe excess and Al toxicity converges at two levels via STOP1 signaling: post-translationally through the regulation of STOP1 turnover, and transcriptionally, via the activation of STOP1-dependent gene expression that enables the root to better adapt to abiotic stress factors present in acidic soils.